APPLICATION OF PICTURE MEDIA IN IMPROVING STUDENTS' LEARNING OUTCOMES IN ENGLISH LESSONS - Beny Arihakam Hakam (JETS: Journal of English Teaching Strategies, 2023)
This study aims to 1) determine the application of audio-visual media in improving learning outcomes. 2) To determine student learning outcomes in thematic lessons. This study is a Classroom Action Research (CLAR) model Kemmis and Mc Taggart. The study was conducted in the second semester of the 2022/2023 academic year in two cycles with three meetings. The subjects of this study were 22 students of class X MA Nurul Ulum The data collection techniques used were observation, tests and documentation. The results of this study indicate that there is an increase in learning outcomes for Thematic Language. The average learning outcomes during the pre-cycle were 65.22, for completeness there were 6 students or 27% and there were 16 students or 63% who had not completed. These results have not met the KKM, which is 70. In cycle I, an increase in the average class result was 72.13, completeness there were 11 students or 50% and 11 students or 50% had not completed, meaning there was an increase in the average value from pre-cycle to cycle one by 23%. Meanwhile, the results of cycle II experienced another increase, namely the class average increased to 85.6 and there were 20 students or 90% who completed and 2 students or 10% who had not completed, thus there was an increase in the average from cycle I to cycle II of 30%.